The Paradigm of Islamic Political Economy as the Basis for Sustainable Development Strategy - Ferdiansyah, Dimas; Apriyanti, Nafisa Nur; Maulana, Lutfi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Current global sustainable development paradigms remain largely influenced by conventional economic approaches that often overlook ethical and spiritual dimensions. This creates a growing need for alternative frameworks that are more holistic and just. This study aims to explore the paradigm of Islamic political economy as a conceptual foundation for sustainable development strategies. A qualitative literature study with an interpretative approach was employed, analyzing relevant primary and secondary sources. The findings reveal that core principles of Islamic political economy—such as distributive justice, maqasid al-shariah, social responsibility, and amanah—hold significant potential in shaping a more human-centered and sustainable development policy framework. This study contributes to the enrichment of Islamic political economy theory and supports the integration of Islamic values in contemporary development practices. Further empirical research is recommended to test the application of this paradigm across various policy contexts. the dominant conventional development paradigm today often ignores spiritual and ethical values, thus creating social and ecological inequalities. This study aims to examine the Islamic political economy paradigm as an alternative basis for sustainable development strategies through a qualitative literature study approach. By examining primary and secondary sources, this study identifies five main principles in Islamic political economy that are relevant to sustainable development: monotheism, justice, benefit, balance, and trust. The results of the study show that this paradigm not only provides a normative foundation, but also a more holistic and equitable policy direction. These findings have implications for the development of development theory and policy formulation based on Islamic values.